Construction of a C@MoS2@C sandwiched heterostructure for accelerating the pH-universal hydrogen evolution reaction. Issue 87 (9th October 2020) - Mei, Yan; Li, Ting-Ting; Qian, Jinjie; Li, Hongwei; Wu, Miao; Zheng, Yue-Qing
Abstract : The sandwich structured PCN@MoS2 @C composite shows remarkable electrocatalytic performance towards the hydrogen evolution reaction over a wide pH range. Abstract : Herein a facile and versatile hydrothermal method has been developed to construct a polypyrrole-derived carbon nanotube (PCN), MoS2 nanosheets and a carbon shell integrated sandwich-like heterostructure (PCN@MoS2 @C). This heterostructure shows excellent performance in the hydrogen evolution reaction (HER) over a wide pH range. The results indicate that the porous carbon shell coated heterostructure provides MoS2 nanosheets with sufficient conductivity, increased number of active sites, and strong structural stability, and thus boosts its HER performance.